2019
DOI: 10.3171/2019.7.focus19434
|View full text |Cite
|
Sign up to set email alerts
|

Progressive hydrocephalus despite early complete reversal of hindbrain herniation after prenatal open myelomeningocele repair

Abstract: OBJECTIVEOpen prenatal myelomeningocele (MMC) repair is typically associated with reversal of in utero hindbrain herniation (HBH) and has been posited to be associated with a reduction in both postoperative prenatal and immediate postnatal hydrocephalus (HCP) risks. However, the long-term postnatal risk of HCP following HBH reversal in these cases has not been well defined. The authors describe the results of a long-term HCP surveillance in a cohort of patients who un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…This is demonstrated in our study, in which 17% of fetuses without significant ventriculomegaly at the last prenatal assessment still required postnatal CSF diversion treatment. Previous research has shown that even fetuses undergoing in‐utero closure and demonstrating an optimal prenatal course and regression of hindbrain herniation may sometimes require CSF diversion surgery, albeit often later in life 14 .…”
Section: Discussionmentioning
confidence: 99%
“…This is demonstrated in our study, in which 17% of fetuses without significant ventriculomegaly at the last prenatal assessment still required postnatal CSF diversion treatment. Previous research has shown that even fetuses undergoing in‐utero closure and demonstrating an optimal prenatal course and regression of hindbrain herniation may sometimes require CSF diversion surgery, albeit often later in life 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Although uncommon, this occurrence has been previously documented. 13 Our patient underwent endoscopic third ventriculostomy with choroid plexus cauterization. The goal with this procedure was to prevent the need for a shunt, because shunting in spina bifida has been shown to be inversely associated with ambulatory status.…”
Section: Discussionmentioning
confidence: 92%
“…Nevertheless, this information is not available at the time of referral, so it cannot be used as part of parental counseling prior to repair. Residual HBH after prenatal ONTD repair has been linked to an increased risk for postnatal hydrocephalus treatment 4,5 ; however, some cases with complete in-utero HBH reversal can also develop progressive hydrocephalus and require postnatal diversion treatment 21 . Gradual-onset hydrocephalus may persist as a sequela of successful HBH reversal with prenatal repair.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that a combination of different predisposing features, including persistent ventriculomegaly, other ventricular changes after ONTD repair, a more cephalad defect and higher intracranial pressure compromising CSP integrity, could affect long-term CSF hydrodynamics, leading to a higher risk for VP shunting after birth 6,21,22 .…”
Section: Discussionmentioning
confidence: 99%